Aminopeptidase N‐Responsive Conjugates with Tunable Charge‐Reversal Properties for Highly Efficient Tumor Accumulation and Penetration. Issue 9 (24th January 2023) - Sun, Rui; Zhang, Yifan; Lin, Xiaowei; Piao, Ying; Xie, Tao; He, Yi; Xiang, Jiajia; Shao, Shiqun; Zhou, Quan; Zhou, Zhuxian; Tang, Jianbin; Shen, Youqing
Abstract: Tumor enzyme‐responsive charge‐reversal carriers can induce efficient transcytosis and lead to efficient tumor infiltration and potent anticancer efficacy. However, the correlations of molecular structure with charge‐reversal property, tumor penetration, and drug delivery efficiency are unknown. Herein, aminopeptidase N (APN)‐responsive conjugates were synthesized to investigate these correlations. We found that the monomeric unit structure and the polymer chain structure determined the enzymatic hydrolysis and charge‐reversal rates, and accordingly, the transcytosis and tumor accumulation and penetration of the APN‐responsive conjugates. The conjugate with moderate APN responsiveness balanced the in vitro transcytosis and in vivo overall drug delivery process and achieved the best tumor delivery efficiency, giving potent antitumor efficacy. This work provides new insight into the design of tumor enzyme‐responsive charge‐reversal nanomedicines for efficient cancer drug delivery. Abstract : Aminopeptidase N (APN)‐responsive charge‐reversal polymer‐drug conjugates with tunable charge‐reversal rates were synthesized. The monomeric unit structure (α‐substituent of the amide) and polymer chain structure determined the enzymatic hydrolysis and charge‐reversal rates, and accordingly, the transcytosis and tumor accumulation and penetration of the APN‐responsive conjugates. The conjugate with moderate APN responsiveness balanced the in vitro and in vivo delivery efficiency and achieved the best antitumor efficacy.